2016
DOI: 10.1159/000442517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry in Identification of Nontuberculous Mycobacteria

Abstract: Background/Aims: Species-level identification of nontuberculous mycobacteria (NTM) is important in making decisions about the necessity and choice of antimicrobial treatment. The reason is predictable clinical significance and the susceptibility profile of specific NTM species. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is recognized as a diagnostic tool for routine identification of bacteria and yeasts in the clinical laboratory based on protein fingerprint ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These studies also lacked uniformity in sample preparation. Samples for mass spectrometry included whole cells in matrix solution (Lin et al, 2013), cells directly applied on MALDI plates (Pignone et al, 2006), non-sonicated cell-free supernatants (Hettick et al, 2006), mechanical breaking of heat-inactivated cells followed by protein extractions with formic acid and acetonitrile (El Khechine et al, 2011) or protein extraction from culture supernatants (Marekovic et al, 2016). Cell lysates were used routinely for MALDI-TOF characterization of foodborne pathogens in our laboratory (Mandrell et al, 2005; Fagerquist et al, 2010; Penny et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also lacked uniformity in sample preparation. Samples for mass spectrometry included whole cells in matrix solution (Lin et al, 2013), cells directly applied on MALDI plates (Pignone et al, 2006), non-sonicated cell-free supernatants (Hettick et al, 2006), mechanical breaking of heat-inactivated cells followed by protein extractions with formic acid and acetonitrile (El Khechine et al, 2011) or protein extraction from culture supernatants (Marekovic et al, 2016). Cell lysates were used routinely for MALDI-TOF characterization of foodborne pathogens in our laboratory (Mandrell et al, 2005; Fagerquist et al, 2010; Penny et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that M. abscessus and other mycobacterial species can be identified by MALDI-TOF MS [7,8,11,12]. In study which compares MALDI-TOF MS and reverse hybridization-based assay for the identification of NTM, the concordance analysis between the two methods showed agreement in 96.9% [7].…”
Section: Abscessusmentioning
confidence: 89%
“…Recently, the introduction of matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) provides a rapid identification for clinical isolates of NTM. The identification ability of MALDI-TOF MS for NTM has been assessed and improved by several studies in various setting of the composition of database, or sample pretreatment [7,8]. Here, we report a rare case of M. abscessus bacteremia in which blood isolates were identified by MALDI-TOF MS.…”
Section: Introductionmentioning
confidence: 98%
“…6 The MALDI-TOF spectrometry method used to identify M. immunogenum in this case, utilizes protein fingerprint analysis to identify bacteria and yeast. 7 M. immunogenum has been implicated as the causative agent in several reported skin infections (Table 1). These cases were observed after penetrating trauma like tattoo needles, medication injections, and intravenous catheters.…”
Section: Case Reportmentioning
confidence: 99%
“…2,4,8 Similar to other NTM, M. immunogenum is capable of contaminating hospital water and equipment due to its resistance to a variety of DISCUSSION disinfectants, biocides, and its ability to form biofilms. 7 In a one study, M. immunogenum was the second most common NTM isolated from swimming pools. Unlike other NTM species, M. immunogenum was not isolated in spas or whirlpools.…”
Section: Case Reportmentioning
confidence: 99%